Analisis Kinerja Keuangan Badan Amil Zakat Nasional Kota Bandung Periode 2020-2021 - Gina Sakinah; Riska Amalia; Ade Ponirah (Jurnal Maps (Manajemen Perbankan Syariah), 2023)
The purpose of this study is to analyze the financial performance of Baznas Kota Bandung. In this study, qualitative and quantitative data analysis techniques use financial performance ratio analysis, which uses two of the four financial performance ratios that have been developed by Puskas BAZNAS (2021), namely Activity and Growth Variables. The results of this study are In terms of activity variables, BAZNAS Bandung City ranked 1st with a score of 0.57. The ranking shows that BAZNAS Bandung City has a very effective ability in distributing Zakat, Infak and Alms funds. In terms of growth variables, BAZNAS Bandung City ranked 2nd with a score of 2.13. The ranking shows that BAZNAS Bandung City has good growth in the collection and distribution of Zakat, Infak and Alms funds. While the Financial performance of BAZNAS Bandung City by adding activity variables with growth variables, BAZNAS Bandung City ranked 1st with a score of 1.19. This ranking shows that BAZNAS Bandung City has excellent financial performance, namely having the ability to manage Zakat, Infak and Alms funds with a very high level of effectiveness and efficiency so that it can grow optimally.